Who Speaks in Memory? Self-Reference, Life-Story, and the Autobiography-Game in Vladimir Nabokov’s Speak, Memory - Zohreh Ramin; Sara Nazockdas (Anglica. An International Journal of English Studies)
As best evidences of our narrative identity language-games, autobiographies unveil the illusive power of language in purporting a unitary self. Drawing upon Ludwig Wittgenstein’s no-reference view of “I” and studying its use as a necessary formal tie in autobiographical memory, it is contended that sense of self through time is constituted in narrating and being narrated in memories. It is argued that Vladimir Nabokov’s Speak, Memory illustrates the lack of reference of the first-person pronoun in autobiographical memory, its formal and inventive emergence, and its diversity in narrative compositions. As the title hints, the self does not speak in memory; it is spoken in autobiographical language-games of composition.